UN GENERAL ASSEMBLY RESOLUTION «PRINCIPLES OF PROTECTION OF MENTALLY ILL PERSONS AND IMPROVEMENT OF PSYCHIATRIC CARE»: MAIN EMPHASIS AND PROBLEMS OF IMPLEMENTATION IN CASES OF PROVIDING PERSONAL PSYCHIATRIC ASSISTANCE IN THE FORCED ORDER - GRABOVSKA, OKSANA (Ehrlich’s Journal, 2024)
Abstract. The article provides a comprehensive analysis of Resolution 46/119 of the UN General Assembly "Principles of protection of mentally ill persons and improvement of psychiatric care" provisions - one of the most important acts in the field of protection of the persons rights suffering from mental illnesses. Gaps in the legal regulation of procedure for consideration and resolution by the courts of cases providing a person with compulsory psychiatric care in domestic legislation of Ukraine and, accordingly, the problems of judicial practice were revealed. Its specific importance for the development of civil society is emphasized, because the level of respect for the rights and fundamental freedoms of persons suffering from mental illnesses indicates the development of society in general. Among the set of standards laid down in the Resolution, the fundamental ones for the implementation of judicial proceedings in cases of providing a person with compulsory psychiatric care are highlighted. The content of main standards for the provision of psychiatric care in a compulsory manner, which is possible only by the decision of a court of civil jurisdiction, in the order of a separate proceeding, in the absence of a person’s informed consent to the provision of psychiatric care, is disclosed. It is noted that the main standards of the Resolution have been taken into account by the legislator and enshrined in the legislation of Ukraine, in particular, in the Law of Ukraine "On Psychiatric Assistance", in the Civil Procedure Code of Ukraine etc. At the same time, not all of important provisions of the Resolution have found their place in national acts, therefore, the need for further legislative work in this direction is emphasized in order to optimize the scope of consideration and resolution by courts of cases of providing a person with compulsory psychiatric care. Additional attention is paid to the problems of judicial practice related to the neglect of the Resolution principles, which leads to the violation of persons rights in respect of whom the courts decide the issue of compulsory psychiatric care, the annulment of court decisions. Special attention is paid to cases of compulsory psychiatric care, through forced hospitalization in a psychiatric care facility, because according to Article 5 of the Convention on the Protection of Human Rights and Fundamental Freedoms of 1950, this method of psychiatric care is a deprivation of a person’s liberty. It is emphasized the need for strict compliance with the Resolution principles, the provisions of national legislation, which mainly correspond to them, precisely in this subcategory of cases, in connection with the urgent problems associated with the violation of persons rights suffering from mental illnesses, during solving the issue of providing psychiatric care.